Posterior dislocation of left hip joint with closed fracture of left acetabulum Judet-Letournel type posterior wall, femoral head fracture, management and follow up: A case report - Dilogo, Ismail Hadisoebroto (Int J Surg Case Rep, 2020)
INTRODUCTION: Traumatic dislocation of the hip is a very severe injury. Posterior hip dislocation can be associated with acetabular fracture, which can ultimately result in a higher incidence of complications. CASE PRESENTATION: We present a case report of 26-year-old men with a motor vehicle accident and suffered a posterior hip dislocation on left hip joint and acetabular fracture with Judet-Letournel type posterior wall and femoral head fracture. This patient was performed closed reduction, however, due to dynamic instability of hip joint, internal Fixation through Kocher Langenback Approach and insertion of Herbert screws for femoral head and acetabular posterior wall fracture and interfragmentary screw for trochanteric osteotomy. The patient was followed up for 2 years and have a painless hip with full hip range of motion. DISCUSSION: Posterior wall acetabular fractures sometimes occurs after posterior dislocation of the hip. Posterior wall fragment of the acetabular wall fracture can compromise the stability of the hip joint. The reduction can be maintained by closed means or by operative reduction if there is an obstacle to performed closed reduction or followed by sciatic nerve palsy after closed reduction. The complication of operative reduction is avascular necrosis which compromises the integrity of the femoral head and contributing to posttraumatic osteoarthritis. CONCLUSION: Careful examination of acetabular fracture in posterior hip dislocation is required and failed of closed reduction or instability of hip joint are indications to perform open reduction and internal fixation.